Positive pole piece of lithium ion battery, preparation method of positive pole piece and lithium ion battery
By using corrosive current collector in the positive electrode sheet of lithium-ion battery, the contact area between the positive electrode and the positive electrode active material layer is increased, the problems of insufficient bonding and powder loss are solved, and the energy density is increased and the cost is reduced by selecting corrosive aluminum foil, which is effective in achieving high bonding, low cost and high energy density.
Patent Information
- Application Number
- CN202311234693.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-03-25
AI Technical Summary
The existing lithium-ion battery positive electrode sheet has powder loss problems during the bonding process, and energy density and cost will be sacrificed when using carbon coated foil, and the main material/auxiliary material matching is poor.
The contact area between the corrosive current collector and the positive electrode active material layer is increased to improve the adhesion force, and by controlling the thickness, surface density and average depth of the corrosive current collector, corrosive aluminum foil is selected to improve energy density and reduce costs.
The bonding force and energy density of the positive electrode sheet of lithium-ion battery is improved, the cost is reduced, and the problem of poor matching of main materials/auxiliary materials is solved, and it is easy to process during welding.
Smart Images

Figure CN119695055A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion secondary batteries, and in particular to a lithium ion battery positive electrode sheet and a preparation method thereof, and a lithium ion battery. Background Art
[0002] With the rapid development of lithium-ion batteries, people's requirements for lithium-ion batteries are constantly changing. Among them, the selection of positive electrode materials is crucial to the performance and cost of lithium-ion batteries. At present, the main materials commonly used for lithium-ion battery positive electrode mass production include ternary, lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, etc. Among them, lithium iron phosphate is gradually applied to energy storage, power batteries and other fields due to its low price, stable material, and good cycle. The particles of lithium iron phosphate are generally nano / submicron powders with the characteristics of small particle size and large specific surface area. Different powder processing processes will cause poor bonding of the corresponding pole pieces. In severe cases, powder loss will occur, affecting the processing of the pole pieces. At present, the current collector commonly used in the production of lithium iron phosphate pole pieces is plain foil or carbon-coated foil. Plain foil does not meet product requirements, and carbon-coated foil will sacrifice a certain energy density, high cost, and poor matching with the main material / auxiliary material in the pole piece.
[0003] Based on this technical background, the present invention proposes a lithium-ion battery positive electrode plate and a preparation method and a lithium-ion battery. The positive electrode plate adopts a corrosion current collector and has the advantages of low cost, high adhesion, and easy processing. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention proposes a lithium ion battery positive electrode plate and a preparation method and a lithium ion battery. The positive electrode plate increases the contact area between the corrosion collector and the positive electrode active material layer, thereby improving the adhesion between the two. At the same time, the current collector with a corrosion surface is also easy to process during welding.
[0005] In order to achieve the above-mentioned object, the present invention provides a lithium-ion battery positive electrode sheet in a first aspect, comprising:
[0006] A corrosion current collector having corrosion surfaces on both sides;
[0007] Two positive electrode active material layers are respectively attached to the two sides of the corrosion current collector.
[0008] A second aspect of the present invention provides a method for preparing the above-mentioned positive electrode sheet, the method comprising the following steps:
[0009] (1) Mixing: Mixing the active material and auxiliary materials to obtain positive electrode slurry;
[0010] (2) coating: uniformly coating the positive electrode slurry on both sides of the corrosion current collector to obtain a coated electrode sheet;
[0011] (3) rolling: rolling the coated electrode sheet to obtain a rolled electrode sheet;
[0012] (4) Sheet making: the rolled electrode sheet is made into a positive electrode sheet.
[0013] A third aspect of the present invention provides a lithium-ion battery having the above-mentioned positive electrode sheet.
[0014] The technical effects of the present invention include:
[0015] (1) The lithium-ion battery positive electrode sheet proposed in the present invention increases the contact area between the current collector and the positive electrode active material layer by corrosion, thereby improving the bonding force between the two. At the same time, the current collector with a corroded surface is also easy to process during welding.
[0016] (2) The lithium-ion battery positive electrode plate proposed in the present invention increases the contact area between the corrosion collector and the positive electrode active material layer by controlling the thickness, surface density and average depth of the corrosion surface of the corrosion collector. At the same time, the corrosion aluminum foil is selected as the corrosion collector, which not only avoids the increase in energy density due to the addition of the uncoated carbon layer, but also solves the problem of poor matching of the main material / auxiliary material in the positive electrode plate.
[0017] (3) The lithium-ion battery positive electrode sheet proposed in the present invention not only improves the adhesion between the corrosion collector and the positive electrode active material layer, but also improves the energy density and electrical performance of the positive electrode sheet by controlling the particle size range and electrical conductivity of the active material.
[0018] (4) The method for preparing the positive electrode sheet of a lithium-ion battery proposed in the present invention optimizes the electrical properties of the positive electrode active material layer by controlling the mass ratio of the active substance, the binder, the conductive agent, the dispersant and the solvent. At the same time, by matching the positive electrode active material layer with the corrosion current collector, the formula system of the positive electrode active material layer has stronger practicality.
[0019] (5) Compared with lithium-ion batteries using rolled plain foil, the lithium-ion battery proposed in the present invention has the advantages of large peeling force after rolling, low electrode interface resistance and battery internal resistance, good rate performance, good cycle performance, and easy processing of the tabs; compared with lithium-ion batteries using carbon-coated foil, the lithium-ion battery proposed in the present invention has the advantages of high peeling force after rolling, low foil cost, high battery energy density, and strong applicability of the formulation system.
[0020] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The above and other objects, features and advantages of the present invention will become more apparent through a more detailed description of exemplary embodiments of the present invention in conjunction with the accompanying drawings, wherein like reference numerals generally represent like components throughout the exemplary embodiments of the present invention.
[0022] Figure 1 This is a schematic diagram of the structure of the positive electrode plate of a lithium-ion battery proposed by the present invention.
[0023] Description of reference numerals:
[0024] 1-corrosion of current collector, 2-positive electrode active material layer. DETAILED DESCRIPTION
[0025] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein.
[0026] In the present invention, unless otherwise specified, directional words such as "upper" and "lower" generally refer to the upper and lower parts of a device in normal use. Figure 1 In the drawing direction, "inside" and "outside" refer to the outline of the device. In addition, the terms "first, second, third" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first, second, third" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0027] The present invention provides a lithium ion battery positive electrode plate, such as Figure 1 As shown, including:
[0028] A corrosion current collector 1, both sides of which have corrosion surfaces;
[0029] Two positive electrode active material layers 2 are respectively attached to two sides of the corrosion current collector 1 .
[0030] In the present invention, the contact area between the current collector 1 and the positive electrode active material layer 2 is increased by corrosion, thereby improving the bonding force between the two. At the same time, the current collector with a corroded surface is also easy to process during welding.
[0031] According to the present invention, the corrosion current collector 1 is a corrosion aluminum foil;
[0032] Each positive electrode active material layer 2 is made by mixing active material and auxiliary material;
[0033] The particle size of the active substance ranges from nanometers to micrometers;
[0034] The positive electrode sheet is obtained by coating, rolling and sheeting the corrosion current collector 1 in sequence;
[0035] The coating is to coat the mixture of the active material and the auxiliary material on both sides of the corrosion current collector 1 respectively;
[0036] Auxiliary materials include a binder, a conductive agent, an optional dispersant and a solvent.
[0037] According to the present invention, the thickness of the corrosion current collector 1 is 5 μm to 15.9 μm, and the surface density is 15 g / m 2 ~50g / m 2 ; The average depth of the corrosion surface is 0.1-10μm.
[0038] In the present invention, the contact area between the corrosion collector 1 and the positive electrode active material layer 2 is increased by controlling the thickness, surface density and average depth of the corrosion surface of the corrosion collector 1. At the same time, the corrosion aluminum foil is selected as the corrosion collector 1, which not only avoids the increase in energy density due to the addition of the non-carbon-coated layer, but also solves the problem of poor matching of the main material / auxiliary material in the positive electrode sheet.
[0039] Preferably, the particle size D50 of the active substance particles is 200 nm to 3 μm.
[0040] Preferably, the conductivity of the active material is 10 -3 S / cm~10 -10 S / cm.
[0041] In the present invention, by controlling the particle size range and conductivity of the active material, not only the bonding force between the corrosion current collector 1 and the positive electrode active material layer 2 is improved, but also the energy density and electrical performance of the positive electrode sheet are improved.
[0042] According to the present invention, the active material is selected from any one of lithium iron phosphate, lithium iron phosphate, ternary composite positive electrode material, elemental sulfur, sulfide, and sulfur-containing mixture;
[0043] Sulfur-containing mixtures are mixtures of elemental sulfur or sulfides and metal oxides or carbides;
[0044] The binder is at least one of polytetrafluoroethylene, polyacrylic acid, polyvinylidene fluoride and polyvinyl pyrrolidone;
[0045] The conductive agent is at least one of conductive carbon black, conductive graphite, carbon nanotubes, graphene, and graphene oxide;
[0046] The dispersant is at least one of an ester compound, a hydroxy compound, an ether compound, an amide compound, and a cyano compound;
[0047] The solvent is at least one of nitrogen methyl pyrrolidone, formamide and acetamide.
[0048] The present invention also provides a method for preparing the above-mentioned positive electrode sheet, which comprises the following steps:
[0049] (1) Mixing: Mixing the active material and auxiliary materials to obtain positive electrode slurry;
[0050] (2) Coating: evenly coating the positive electrode slurry on both sides of the corrosion current collector 1 to obtain a coated electrode sheet;
[0051] (3) Rolling: Rolling the coated electrode to obtain a rolled electrode;
[0052] (4) Sheet making: Roll-press the electrode sheet to make the positive electrode sheet.
[0053] Preferably, the mass ratio of active material, binder, conductive agent, dispersant and solvent is 80-100: 1.0-5.5: 0.5-5.5: 0-0.9: 42-120;
[0054] The coating method is extrusion coating, with a surface density of 30-500g / m 2 ;
[0055] The thickness of the rolled pole piece is 40-200μm;
[0056] The size of the positive electrode plate is 5mm-20m in length and 5mm-1400mm in width, and the shape is a plate or a coil.
[0057] In the present invention, the electrical properties of the positive electrode active material layer 2 are optimized by controlling the mass ratio of the active substance, the binder, the conductive agent, the dispersant and the solvent. At the same time, by matching the positive electrode active material layer 2 with the corrosion current collector 1, the formula system of the positive electrode active material layer 2 has stronger practicality.
[0058] The present invention also provides a lithium ion battery having the positive electrode plate.
[0059] Preferably, the lithium-ion battery is a soft-pack battery, and its shape is any one of square, cylindrical or irregular.
[0060] Compared with lithium ion batteries using rolled plain foil, the lithium ion battery in the present invention has the advantages of large peeling force after rolling, low electrode interface resistance and battery internal resistance, good rate performance, good cycle performance, and easy processing of the tabs; compared with lithium ion batteries using carbon-coated foil, the lithium ion battery in the present invention has the advantages of high peeling after rolling, low foil cost, high battery energy density, and strong applicability of the formulation system.
[0061] The present invention will be described in more detail below through specific embodiments.
[0062] Example 1
[0063] In this embodiment, the same positive electrode slurry is used to coat, roll-press, make sheets and manufacture batteries on carbon-coated aluminum foil, corroded aluminum foil and bare aluminum foil in turn, and the peeling strength of each electrode sheet after coating is compared and tested, and the peeling strength of each electrode sheet after rolling is compared and tested, and the battery obtained by battery manufacturing is compared and tested on the electrode ear welding tensile strength, AC internal resistance and DC internal resistance. The specific implementation steps are as follows:
[0064] (1) Mixing: Lithium iron phosphate, polyvinylidene fluoride, carbon nanotubes, conductive carbon black, and nitrogen methyl pyrrolidone were mixed in a weight ratio of 96.5:1.8:0.5:1.2:65 to prepare a positive electrode slurry, wherein the lithium iron phosphate D50 particle size was 1.2 μm and the conductivity was 5.6*10 -6 S / cm;
[0065] (2) Coating: The positive electrode slurry was uniformly coated on the carbon-coated aluminum foil, corroded aluminum foil and plain aluminum foil current collectors, and the single-sided coating thickness was 94 μm. The thicknesses of the carbon-coated aluminum foil, corroded aluminum foil and plain aluminum foil current collectors were 15 μm, 13 μm and 13 μm, respectively, and the surface densities were 36.13 g / m 2 , 35.23g / m 2 , 35.05g / m 2 , where the average depth of the corroded surface of the aluminum foil is 1μm. The peel strength of each electrode after coating is tested, and the data are as follows:
[0066] Foil Type Carbon coated aluminum foil Corrosion of aluminum foil Light Aluminum Foil Peel strength (N / m) 10 8 5
[0067] By comparison, it can be seen that the order of peel strength of each electrode after coating is: carbon-coated aluminum foil > corroded aluminum foil > plain aluminum foil;
[0068] (3) Rolling: Each electrode after coating is rolled to 165 μm, and the compaction density is 2.45 g / cm 3 , after rolling, the peel strength and resistance of each electrode were tested, and the data are as follows:
[0069] Foil Type Carbon coated aluminum foil Corrosion of aluminum foil Light Aluminum Foil Peel strength (N / m) 12 20 6
[0070] By comparison, it can be seen that the order of peeling strength of each electrode after rolling is: corroded aluminum foil > carbon-coated aluminum foil > plain aluminum foil;
[0071] The resistance of each electrode after rolling is tested, and the data are as follows:
[0072] Foil Type Carbon coated aluminum foil Corrosion of aluminum foil Light Aluminum Foil Pole interface resistance (Ωcm2) 0.0679 0.0363 5.51
[0073] By comparison, it can be seen that the order of resistance of each electrode after rolling is: plain aluminum foil > carbon-coated aluminum foil > corroded aluminum foil;
[0074] (4) Sheeting: Each rolled electrode sheet is made into a positive electrode sheet with a length of 195 mm and a width of 150 mm, wherein each positive electrode sheet has 36 sheets and the paired negative electrode sheet has 37 sheets;
[0075] (5) Battery production: Each positive electrode sheet and its paired negative electrode sheet were made into a 50Ah soft-pack battery cell, and the tab welding tensile strength test was performed on each soft-pack battery cell. The data are as follows:
[0076] Foil Type Carbon coated aluminum foil Corrosion of aluminum foil Light Aluminum Foil Tab welding tensile strength (N / mm) 3.5 3.8 3.5
[0077] By comparison, it can be seen that the order of the tensile strength of the welding lugs of each soft-pack battery cell is: corroded aluminum foil > carbon-coated aluminum foil ≈ plain aluminum foil;
[0078] The AC internal resistance test of each soft-pack battery cell is carried out, and the data are as follows:
[0079] Foil Type Carbon coated aluminum foil Corrosion of aluminum foil Light Aluminum Foil Battery AC internal resistance (mΩ) 0.5579 0.5432 2.6584
[0080] By comparison, it can be seen that the order of the AC internal resistance of each soft-pack battery cell is: plain aluminum foil > carbon-coated aluminum foil ≈ corroded aluminum foil;
[0081] The DC internal resistance test of each soft-pack battery cell is carried out, and the data are as follows:
[0082] Foil Type Carbon coated aluminum foil Corrosion of aluminum foil Light Aluminum Foil Battery DCIR(mΩ) 1.157 1.037 4.386
[0083] By comparison, it can be seen that the order of the DC internal resistance of each soft-pack battery cell is: plain aluminum foil > carbon-coated aluminum foil ≈ corroded aluminum foil
[0084] Example 2
[0085] In this embodiment, the same positive electrode slurry is used to coat, roll-press, make sheets and manufacture batteries on carbon-coated aluminum foil, corroded aluminum foil and bare aluminum foil in turn, and the peeling strength of each electrode sheet after coating is compared and tested, and the peeling strength of each electrode sheet after rolling is compared and tested, and the battery obtained by battery manufacturing is compared and tested on the electrode ear welding tensile strength, AC internal resistance and DC internal resistance. The specific implementation steps are as follows:
[0086] (1) Mixing: Lithium iron phosphate, polyvinylidene fluoride, carbon nanotubes, conductive carbon black, and nitrogen methyl pyrrolidone are mixed in a weight ratio of 96.5:1.8:0.5:1.2:65 to prepare a positive electrode slurry, wherein the D50 particle size of the lithium iron phosphate material is 0.9 μm and the conductivity is 1.2*10 -6 S / cm;
[0087] (2) Coating: The positive electrode slurry was uniformly coated on the carbon-coated aluminum foil, the corroded aluminum foil and the plain aluminum foil current collectors, and the single-sided coating thickness was 93.5 μm. The thicknesses of the carbon-coated aluminum foil, the corroded aluminum foil and the plain aluminum foil current collectors were 15 μm, 13 μm and 13 μm, respectively, and the surface densities were 36.13 g / m 2 , 35.23g / m 2 , 35.05g / m 2 , where the average depth of the corroded surface of the aluminum foil is 1μm. The peel strength of each electrode after coating is tested, and the data are as follows:
[0088] Foil Type Carbon coated aluminum foil Corrosion of aluminum foil Light Aluminum Foil Peel strength (N / m) 9.6 8.2 4.2
[0089] By comparison, it can be seen that the order of peel strength of each electrode after coating is: carbon-coated aluminum foil > corroded aluminum foil > plain aluminum foil;
[0090] (3) Rolling: Each electrode after coating is rolled to 163 μm, and the compaction density is 2.42 g / cm 3 , after rolling, the peel strength and resistance of each electrode were tested, and the data are as follows:
[0091] Foil Type Carbon coated aluminum foil Corrosion of aluminum foil Light Aluminum Foil Peel strength (N / m) 11 18.6 5.4
[0092] By comparison, it can be seen that the order of peeling strength of each electrode after rolling is: corroded aluminum foil > carbon-coated aluminum foil > plain aluminum foil;
[0093] The resistance of each electrode after rolling is tested, and the data are as follows:
[0094] Foil Type Carbon coated aluminum foil Corrosion of aluminum foil Light Aluminum Foil Pole interface resistance (Ωcm2) 0.0653 0.0342 4.623
[0095] By comparison, it can be seen that the order of resistance of each electrode after rolling is: plain aluminum foil > carbon-coated aluminum foil > corroded aluminum foil;
[0096] (4) Sheeting: Each rolled electrode sheet is made into a positive electrode sheet with a length of 195 mm and a width of 150 mm, wherein each positive electrode sheet has 36 sheets and the paired negative electrode sheet has 37 sheets;
[0097] (5) Battery production: Each positive electrode sheet and its paired negative electrode sheet were made into a 50Ah soft-pack battery cell, and the tab welding tensile strength test was performed on each soft-pack battery cell. The data are as follows:
[0098] Foil Type Carbon coated aluminum foil Corrosion of aluminum foil Light Aluminum Foil Tab welding tensile strength (N / mm) 3.45 3.82 3.46
[0099] By comparison, it can be seen that the order of the tensile strength of the welding lugs of each soft-pack battery cell is: corroded aluminum foil > carbon-coated aluminum foil ≈ plain aluminum foil;
[0100] The AC internal resistance test of each soft-pack battery cell is carried out, and the data are as follows:
[0101] Foil Type Carbon coated aluminum foil Corrosion of aluminum foil Light Aluminum Foil Battery AC internal resistance (mΩ) 0.5468 0.5129 2.739
[0102] By comparison, it can be seen that the order of the AC internal resistance of each soft-pack battery cell is: plain aluminum foil > carbon-coated aluminum foil ≈ corroded aluminum foil;
[0103] The DC internal resistance test of each soft-pack battery cell is carried out, and the data are as follows:
[0104]
[0105]
[0106] By comparison, it can be seen that the order of the DC internal resistance of each soft-pack battery cell is: plain aluminum foil > carbon-coated aluminum foil ≈ corroded aluminum foil.
[0107] Example 3
[0108] In this embodiment, the same positive electrode slurry is used to coat, roll-press, make sheets and manufacture batteries on carbon-coated aluminum foil, corroded aluminum foil and bare aluminum foil in turn, and the peeling strength of each electrode sheet after coating is compared and tested, and the peeling strength of each electrode sheet after rolling is compared and tested, and the battery obtained by battery manufacturing is compared and tested on the electrode ear welding tensile strength, AC internal resistance and DC internal resistance. The specific implementation steps are as follows:
[0109] (1) Mixing: Lithium iron phosphate, polyvinylidene fluoride, carbon nanotubes, conductive carbon black, and nitrogen methyl pyrrolidone were mixed in a weight ratio of 96.5:1.8:0.5:1.2:65 to prepare a positive electrode slurry, wherein the D50 particle size of the lithium iron phosphate material is 0.78 μm and the conductivity is 8.2*10 -5 S / cm;
[0110] (2) Coating: The positive electrode slurry was uniformly coated on the carbon-coated aluminum foil, corroded aluminum foil and plain aluminum foil current collectors, and the single-sided coating thickness was 93 μm. The thicknesses of the carbon-coated aluminum foil, corroded aluminum foil and plain aluminum foil current collectors were 15 μm, 13 μm and 13 μm, respectively, and the surface densities were 36.13 g / m 2 , 35.23g / m 2 , 35.05g / m 2 , where the average depth of the corroded surface of the aluminum foil is 1μm. The peel strength of each electrode after coating is tested, and the data are as follows:
[0111] Foil Type Carbon coated aluminum foil Corrosion of aluminum foil Light Aluminum Foil Peel strength (N / m) 9.4 8.2 4.1
[0112] By comparison, it can be seen that the order of peel strength of each electrode after coating is: carbon-coated aluminum foil > corroded aluminum foil > plain aluminum foil;
[0113] (3) Rolling: Each electrode after coating is rolled to 163 μm, and the compaction density is 2.42 g / cm 3 , after rolling, the peel strength and resistance of each electrode were tested, and the data are as follows:
[0114]
[0115]
[0116] By comparison, it can be seen that the order of peeling strength of each electrode after rolling is: corroded aluminum foil > carbon-coated aluminum foil > plain aluminum foil;
[0117] The resistance of each electrode after rolling is tested, and the data are as follows:
[0118] Foil Type Carbon coated aluminum foil Corrosion of aluminum foil Light Aluminum Foil Pole interface resistance (Ωcm2) 0.0679 0.0363 5.51
[0119] By comparison, it can be seen that the order of resistance of each electrode after rolling is: plain aluminum foil > carbon-coated aluminum foil > corroded aluminum foil;
[0120] (4) Sheeting: Each rolled electrode sheet is made into a positive electrode sheet with a length of 195 mm and a width of 150 mm, wherein each positive electrode sheet has 36 sheets and the paired negative electrode sheet has 37 sheets;
[0121] (5) Battery production: Each positive electrode sheet and its paired negative electrode sheet were made into a 50Ah soft-pack battery cell, and the tab welding tensile strength test was performed on each soft-pack battery cell. The data are as follows:
[0122] Foil Type Carbon coated aluminum foil Corrosion of aluminum foil Light Aluminum Foil Tab welding tensile strength (N / mm) 3.51 3.83 3.52
[0123] By comparison, it can be seen that the order of the tensile strength of the welding lugs of each soft-pack battery cell is: corroded aluminum foil > carbon-coated aluminum foil ≈ plain aluminum foil;
[0124] The AC internal resistance test of each soft-pack battery cell is carried out, and the data are as follows:
[0125] Foil Type Carbon coated aluminum foil Corrosion of aluminum foil Light Aluminum Foil Battery AC internal resistance (mΩ) 0.5258 0.5029 2.6398
[0126] By comparison, it can be seen that the order of the AC internal resistance of each soft-pack battery cell is: plain aluminum foil > carbon-coated aluminum foil ≈ corroded aluminum foil;
[0127] The DC internal resistance test of each soft-pack battery cell is carried out, and the data are as follows:
[0128] Foil Type Carbon coated aluminum foil Corrosion of aluminum foil Light Aluminum Foil Battery DC internal resistance (mΩ) 1.103 1.002 4.389
[0129] By comparison, it can be seen that the order of the DC internal resistance of each soft-pack battery cell is: plain aluminum foil > carbon-coated aluminum foil ≈ corroded aluminum foil.
[0130] It can be seen from Examples 1-3 of the present application that after coating, the peeling strength of each electrode piece is the largest for the carbon-coated aluminum foil, and the smallest for the bare aluminum foil. After rolling, the peeling strength of the corroded aluminum foil is significantly increased, and at the same time, the interface internal resistance of the corroded aluminum foil is the smallest; the battery obtained by corroding the aluminum foil has the largest electrode ear welding tensile strength, and the smallest AC internal resistance and DC internal resistance.
[0131] In the embodiments 1-3 of the present application, the positive electrode plates of lithium-ion batteries utilize the corrosion of the current collector to increase the contact area with the positive electrode active material layer, thereby improving the bonding force between the two. At the same time, the current collector with a corroded surface is also easy to process during welding.
[0132] The lithium-ion batteries made of corroded aluminum foil in Examples 1-3 of the present application have the advantages of large peeling force after rolling, low electrode interface resistance and battery internal resistance, good rate performance, good cycle performance, and easy processing of the tabs, compared with lithium-ion batteries using rolled plain foil; compared with lithium-ion batteries using carbon-coated foil, they have the advantages of high peeling after rolling, low foil cost, high battery energy density, and strong applicability of the formulation system.
[0133] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A positive electrode plate for a lithium-ion battery, characterized in that: include: A corrosion current collector having corrosion surfaces on both sides; Two positive electrode active material layers are respectively attached to the two sides of the corrosion current collector.
2. The positive electrode sheet according to claim 1, characterized in that: The corrosion current collector is corrosion aluminum foil; Each positive electrode active material layer is prepared by mixing active material and auxiliary material; The particle size of the active substance ranges from nanometers to micrometers; The positive electrode sheet is obtained by sequentially coating, rolling and sheeting the corrosion current collector; The coating is to coat the mixture of the active material and the auxiliary material on both sides of the corrosion current collector respectively; The auxiliary materials include a binder, a conductive agent, an optional dispersant and a solvent.
3. The positive electrode sheet according to claim 1 or 2, characterized in that: The thickness of the corrosion current collector is 5 μm to 15.9 μm, and the surface density is 15 g / m 2 ~50g / m 2 ; The average depth of the corrosion surface is 0.1-10μm.
4. The positive electrode sheet according to claim 2, characterized in that: The particle size D50 of the active material particles is 200 nm to 3 μm.
5. The positive electrode sheet according to claim 2, characterized in that: The conductivity of the active material is 10 -3 S / cm~10 -10 S / cm.
6. The positive electrode sheet according to claim 2, characterized in that: The active material is selected from any one of lithium iron phosphate, lithium iron phosphate, ternary composite positive electrode material, elemental sulfur, sulfide, and sulfur-containing mixture; The sulfur-containing mixture is a mixture of elemental sulfur or sulfide and metal oxide or carbide; The binder is at least one of polytetrafluoroethylene, polyacrylic acid, polyvinylidene fluoride and polyvinyl pyrrolidone; The conductive agent is at least one of conductive carbon black, conductive graphite, carbon nanotubes, graphene, and graphene oxide; The dispersant is at least one of an ester compound, a hydroxy compound, an ether compound, an amide compound, and a cyano compound; The solvent is at least one of nitrogen methyl pyrrolidone, formamide and acetamide.
7. A method for preparing a positive electrode sheet according to any one of claims 2 to 6, characterized in that: The preparation method comprises the following steps: (1) Mixing: Mixing the active material and auxiliary materials to obtain positive electrode slurry; (2) coating: uniformly coating the positive electrode slurry on both sides of the corrosion current collector to obtain a coated electrode sheet; (3) rolling: rolling the coated electrode sheet to obtain a rolled electrode sheet; (4) Sheet making: the rolled electrode sheet is made into a positive electrode sheet.
8. The method for preparing a positive electrode sheet according to claim 7, characterized in that: The mass ratio of the active material, the binder, the conductive agent, the dispersant and the solvent is 80-100: 1.0-5.5: 0.5-5.5: 0-0.9: 42-120; The coating method is extrusion coating, and the surface density is 30-500g / m 2 ; The thickness of the rolled electrode sheet is 40-200 μm; The dimensions of the positive electrode plate are 5mm-20m in length and 5mm-1400mm in width, and the shape is a plate or a coil.
9. A lithium ion battery having the positive electrode sheet according to any one of claims 1 to 6.
10. The lithium ion battery according to claim 9, characterized in that: The lithium-ion battery is a soft-pack battery, and its shape is any one of square, cylindrical or special-shaped.